A Teaching OSCE to Assess Trauma Resident Skills on How to Hold Difficult Conversations With Family of Critically Injured Patients - Sangeeta Lamba; Sarah Bryczkowski; Bart Holland; Roxanne Nagurka; Anne Mosenthal (Association of American Medical Colleges, 2016)
Abstract Introduction Traumatic injury often results in death or significant disability to a previously healthy person, leaving family overwhelmed. Effective communication to support family is therefore important, yet there is little emphasis placed on developing communication skills around death and dying in the trauma setting. Assessment of a resident's communication skills or feedback regarding these skills is rare to nonexistent in emergency medicine and surgery resident training. We designed a curriculum to teach and assess communication skills that address difficult conversations in the trauma bay, which includes this teaching objective structured clinical examination (TOSCE) used to assess communication skills. Methods After a brief introduction and orientation to peer feedback, residents were divided into groups of three to complete two 7-minute TOSCEs, where one resident interacts with a standardized patient (SP) and the other two observe. Communication and overall demeanor are assessed using a checklist format and on a Likert-type scale. The same form was used by the learner, the SP, and the facilitator. SPs assessed residents, and peers/preceptors provided formative feedback. Results Twenty-five residents (nine emergency medicine, 16 surgery) participated in the TOSCE. A majority of participating residents were rated by the standardized patients as competent to perform independently, while a small percentage needed more basic instruction. For the two case scenarios used, SPs rated nearly all residents as competent to perform delivery of poor prognosis and competent or mostly competent to perform delivery of news of death. Mean ratings showed concordance between self-ratings and SP ratings. A majority of residents reported the TOSCE was a valuable learning experience. Discussion In conclusion, a TOSCE is effective in assessing communication skills around the critically injured patient in the trauma bay. A TOSCE is feasible to implement in surgery and emergency medicine residency training, and the format is valued by participants.